The Effect of Stabilization and Strengthening Exercises on Back Pain - Rūta Jankauskaitė; Saulė Sipavičienė (Lithuanian Sports University, 2020)
Background. Back pain is one of the most common health issue worldwide. Physical therapy is the most appropriate intervention to treat nonspecific lower back pain. However, the most effective form of exercise is unknown. The aim of research was to determine the effect of different physical therapy programs for people with low back pain on functional status, pain intensity and quality of life. Methods. Patients who have chronic nonspecific low back pain participated in the research. They were randomly divided into two groups. All of them were getting electrotherapy and physical therapy. Both of the groups were getting strengthening exercises program, group 2 additionally received lumbar stabilization exercises. The following research methods were used: assessment of trunk mobility, trunk muscle static endurance, pain, functional status (Roland Morris, Oswestry questionnaires), quality of life (EQ-5D questionnaire). Data was analyzed using statistical analysis "MS Office Excel 2013", "R x64 3.4.0" programs. Results. After physical therapy, the pain, functional status, disability and health related quality of life parameters improved statistically significantly (p < 0.05). There was no statistically significant difference between the two exercise groups in all parameters (p > 0.05). Conclusions. Lumbar stabilization and strengthening exercise program and only strengthening program were found to have significant positive effects on pain, functional status and quality of life. No statistically significant difference was found between two physical therapy programs for lumbar spine mobility, trunk muscle static endurance, functional status, back pain and quality of life. Keywords: strengthening exercises, physical therapy, lumbar stabilization exercises, back pain.